ModE-Dependent Molybdate Regulation of the Molybdenum Cofactor Operon moa in Escherichia coli - Anderson, Lisa A. (American Society for Microbiology, 2000)
The expression of the moa locus, which encodes enzymes required for molybdopterin biosynthesis, is enhanced under anaerobiosis but repressed when the bacterium is able to synthesize active molybdenum cofactor. In addition, moa expression exhibits a strong requirement for molybdate. The molybdate enhancement of moa transcription is fully dependent upon the molybdate-binding protein, ModE, which also mediates molybdate repression of the mod operon encoding the high-affinity molybdate uptake system. Due to the repression of moa in molybdenum cofactor-sufficient strains, the positive molybdate regulation of moa is revealed only in strains unable to make the active cofactor. Transcription of moa is controlled at two sigma-70-type promoters immediately upstream of the moaA gene. Deletion mutations covering the region upstream of moaA have allowed each of the promoters to be studied in isolation. The distal promoter is the site of the anaerobic enhancement which is Fnr-dependent. The molybdate induction of moa is exerted at the proximal promoter. Molybdate-ModE binds adjacent to the −35 region of this promoter, acting as a direct positive regulator of moa. The molybdenum cofactor repression also appears to act at the proximal transcriptional start site, but the mechanism remains to be established. Tungstate in the growth medium affects moa expression in two ways. Firstly, it can act as a functional molybdate analogue for the ModE-mediated regulation. Secondly, tungstate brings about the loss of the molybdenum cofactor repression of moa. It is proposed that the tungsten derivative of the molybdenum cofactor, which is known to be formed under such conditions, is ineffective in bringing about repression of moa. The complex control of moa is discussed in relation to the synthesis of molybdoenzymes in the bacterium.